Determining Cross-Cultural Mentorship Readiness in Counselor Education and Supervision Programs - Jody Vernam; Brian Paulson; Bridger D Falkenstien; Lynn Bohecker; Nivischi Edwards (Teaching and Supervision in Counseling, 2022)
Abstract: Counselor Education and Supervision (CES) faculty are challenged to include cross-cultural mentorship within CES programs. Successfully implementing cross-cultural mentoring in CES programs requires assessing institutional and CES program readiness and identifying successful strategies. This article outlines a proposed framework to evaluate requisites for cross-cultural mentorship across levels of institutions of higher education and provides strategies to help CES faculty successfully engage and sustain cross-cultural mentorship. What is the public significance of this article? Society and educational programs continue to grow in cultural, racial, and ethnic diversity. As a result, counselor education programs and the systems within which they function will need to adapt to meet the needs of a diverse population of professional counselors, students, and counselor educators. This article enriches the ongoing dialogue on competent cross-cultural mentorship within counselor education programs across various system levels.
Keywords: readiness evaluation model; courageous conversations; cross-cultural mentorship; cultural competency; counselor education